Paper princess - Watt, Erin (The royals, 2023)
"The TikTok sensation Paper Princess, the first in the #1 New York Times bestselling The Royals series, now in a new special edition with bonus material! From strip clubs and truck stops to southern coast mansions and prep schools, one girl tries to stay true to herself. These Royals will ruin you... Ella Harper is a survivor-a pragmatic optimist. She's spent her whole life moving from town to town with her flighty mother, struggling to make ends meet and believing that someday she'll climb out of the gutter. After her mother's death, Ella is truly alone. Until Callum Royal appears, plucking Ella out of poverty and tossing her into his posh mansion among his five sons who all hate her. Each Royal boy is more magnetic than the last, but none as captivating as Reed Royal, the boy who is determined to send her back to the slums she came from. Reed doesn't want her. He says she doesn't belong with the Royals. He might be right. Wealth. Excess. Deception. It's like nothing Ella has ever experienced, and if she's going to survive her time in the Royal palace, she'll need to learn to issue her own Royal decrees"--